CHARACTER BUILDING AS ONE OF THE FOCUSES OF NATIONAL DEVELOPMENT PLANNING IN INDONESIAN LEGISLATION - Susmayanti, Riana (PUSAT MPK UNIVERSITAS BRAWIJAYA, 2023)
Character building is the foundation for realizing the vision of national development, which is to create a noble, moral, ethical, cultured, and civilized society based on the philosophy of Pancasila. Based on this background, the legal issues in this research are: 1) What is the object of character buildingÂ that become the focus of national development planning? and 2) How is character building regulated in legislation? This research uses a statutory approach and a conceptual approach. The objects of character buildingÂ that becomes the focus of national development planning are the character building of children, youth and the State Civil Apparatus. Character building is regulated in several regulations, namely: Law No. 5 of 2014 on State Civil Apparatus, Amendment to Child Protection Law, Amendment to the Marriage Law, Law No. 18 of 2019 on the Islamic Boarding Schools, Law No. 11 of 2022 concerning Sport, Law No. 12 of 2022 on the Sexual Violence Crimes and Law No. 23 of 2022 on the Psychology Education and Services.